RELIABILITY ANALYSIS FOR A FEEDER OF AN ELECTRIC POWER DISTRIBUTION COMPANY IN ECUADOR USING THE MONTE CARLO SIMULATION METHOD (2023)
The present study focuses on the analysis of the reliability indices for the distribution feeder belonging to an Ecuadorian electricity distribution company, reliability analysis is currently a topic of vital importance when making decisions in the area. technique for the electrical supply, in this way, in the first instance, a general evaluation of the feeder is carried out with the objective of collecting important information focused on; areas of influence, global indicators, failures and their causes. With the collection of information, we proceed to design a computational algorithm in the Matlab environment following the Montecarlo simulation methodology because this allows us to evaluate complex mathematical expressions with greater accuracy, concluding with results that allow us to estimate the reliability in the feeder. in order to take actions in the future in order to improve the reliability of the feeder.